Strategi Peningkatan Kompetensi Guru SMK Dalam Konteks Pemenuhan Standar Industri - Enci Zarkasih (Universitas Mathla'ul Anwar Banten, 2018)
THE STRATEGY OF SMK TEACHER COMPETENCY IMPROVEMENT IN THE CONTEXT OF INDUSTRIAL STANDARDS FULFILLMENT. The aim of this research are: to find out the strategic effort in increasing SMK teacher’s competency of SMK, in order to produce SMK graduated base on Industry Standard. We used three theory; 1) Hard and soft skill theory; 2) SMK Teacher`s Competency; 3) Strategic Planning, management and thinking; Qualitative descriptive is more compatible we are used in this research, to explore some information, especially some hidden information; The result of this research are: honesty, attitude, leadership, positive thinking, hard worker, team building, etc.; 2) The teacher`s competency are needed to produce SMK graduated while high competency, included: a) Competency to accomodir what the industry are needed; b) How to translate it to curriculum, syllabus and RPP; How to redesign education`s system base on industry`s system, in order to produce SMK graduated based on industry; 3) There are some strategic to increase SMK teacher competency, included: a) Give more reward; b) Redesign effort in increasing teacher competency, base on financial perspective, customer perspective, internal organization perspective and growth perspective; c) Involved the teacher in discussing prose`s with all company in redesign curriculum and education process; d) Redesign environment that give the teacher`s opportunity to increase their competency; e) Redesign evaluation system; f) Redesign clear criteria for SMK teacher evaluation; g) Headmaster must to develop humanism leadership and give more attention to SMK to increase teacher attitude; h) Conducted discussion process with all teacher in the education institution to increase their competency based on industry needed.